1994
DOI: 10.1016/0735-1097(94)90285-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of residual perfusion within the infarct zone on the natural history of left ventricular dysfunction after acute myocardial infarction: A myocardial contrast echocardiographic study

Abstract: Among patients with a predischarge patent infarct-related artery, further improvement in regional and global function may be expected during follow-up when residual perfusion in the infarct zone is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 39 publications
2
36
0
1
Order By: Relevance
“…This prognosis is even as poor as ir the vessels never had been opened [15]. Using contrast echocardiography, ir has been demonstrated, that despite reopening of coronary vessels in acute myocardial infarction full restoration of myocardial perfusion is incomplete in part of the patients [5,117,120,121,239]. Areas with incomplete restoration of flow reduced of no contrast enhancement of the myocardium in echocardiography have less improvement of ventricular function than areas with complete opacification.…”
Section: Acute Myocardial Infarctionmentioning
confidence: 92%
“…This prognosis is even as poor as ir the vessels never had been opened [15]. Using contrast echocardiography, ir has been demonstrated, that despite reopening of coronary vessels in acute myocardial infarction full restoration of myocardial perfusion is incomplete in part of the patients [5,117,120,121,239]. Areas with incomplete restoration of flow reduced of no contrast enhancement of the myocardium in echocardiography have less improvement of ventricular function than areas with complete opacification.…”
Section: Acute Myocardial Infarctionmentioning
confidence: 92%
“…A rapid definition of the efficacy of reperfusion therapy as well as the extent of its residual microvascular damage has important implications for the treatment of acute myocardial infarction. It has been previously demonstrated that the presence of preserved microvascular flow in the post-reperfusion period is associated with a lower rate of fibrous scar and less ventricular remodeling (32)(33)(34)(35). Thus the differentiation between stunned and infarcted myocardium by RTMCE has important clinical and prognostic implications.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant advantage is that it can be applied in the setting of AMI. The no-reflow phenomenon is detected by contrast echocardiography in 16% of patients with TIMI grade 3 flow (29). Contrast echocardiography was chosen by Agati et al (29) as a tool to prove superiority of primary PCI over thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The no-reflow phenomenon is detected by contrast echocardiography in 16% of patients with TIMI grade 3 flow (29). Contrast echocardiography was chosen by Agati et al (29) as a tool to prove superiority of primary PCI over thrombolytic therapy. Kamp et al (12) carried out serial MCE in patients after primary PCI, showing that a significant reduction in size of the initial perfusion defect predicts functional recovery after four weeks; these findings underscore the potential diagnostic value of the method.…”
Section: Discussionmentioning
confidence: 99%